Keuangan Inklusif Bank Umum Syariah Dalam Mendukung Usaha Mikro Kecil dan Menengah - Erna Wati (AL-FALAH : Journal of Islamic Economics, 2016)
This study examines the financial inclusive SMEs on Indonesian Islamic Commercial Bank (ICB). Data used is secondary data from the publication of the Financial Services Authority (FSA) and the publication of ICB. The indicators examined including of the dimensions of use, physical accessibility and price affordability. The results showed that the preferences of ICB on SMEs access were not related with the size of the bank. The three largest ICB is more lower preference allocation to SMEs. Although Islamic banking office network experienced an increasing trend, but physical accessibility for regency still limited. SMEs still have a low price affordability, contrary to the Shariah Rural Bank (SRB). The results also showed that the lower price affordability the higer NPF of SMEs, which implies trade off between price affordability and collectability of financing. Keywords : Inclusive Finance, Physical Accessibility, Affordability, Dimension Usage